2020
DOI: 10.1002/suco.201900086
|View full text |Cite
|
Sign up to set email alerts
|

Influence of basalt fibers on the mechanical behavior of concrete—A review

Abstract: The natural fibers are evolving in the construction industry in many forms due to its dominant characteristics since decades. This paper delivers a review of the behavior of basalt fiber reinforced concrete under static and dynamic loading conditions. The main aim of the paper is to signify the influence of basalt fibers in concrete as chopped fibers, minibars, rebars, and meshes by showcasing the physical and mechanical properties of the concrete. The proposed review paper furnishes a summary of obtainable ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 68 publications
1
28
0
1
Order By: Relevance
“…Furthermore, we found that existing models could not fully represent the bond‐slip behavior between BFRP bars and basalt‐fiber reinforced cement‐based composite materials, and a new high‐precision bond‐slip model was established. This research on BFFRCC not only solves the problem of brittle fractures in normal work, but also provides some theoretical support for fiber‐reinforced concrete materials 22 …”
Section: Introductionmentioning
confidence: 75%
“…Furthermore, we found that existing models could not fully represent the bond‐slip behavior between BFRP bars and basalt‐fiber reinforced cement‐based composite materials, and a new high‐precision bond‐slip model was established. This research on BFFRCC not only solves the problem of brittle fractures in normal work, but also provides some theoretical support for fiber‐reinforced concrete materials 22 …”
Section: Introductionmentioning
confidence: 75%
“…The total strain (autogenous and thermal) is numerically implanted in the UEXPAN user subroutine. In order to account for cracks appearances in the HSC and even at the reinforcement/concrete interface, the currently used Mazars's elastic‐damageable model is adopted 33,34 . In this model, Young's modulus, Poisson's coefficient, and damage parameters are assumed to evolve depending on the hydration degree.…”
Section: Resultsmentioning
confidence: 99%
“…However, other studies 30–32 had demonstrated that in real‐field conditions, the GFRP durability is not affected in the alkaline environment of concrete and that did not cause any mechanical properties degradation. Another type of FRP rebar which is the basalt one are performed also by their resistivity to the alkaline and saline environments 33,34 . Recently, Salah‐Eddine et al 35 developed an analytical study to predict the axial‐ and flexural‐load capacity of the GFRP‐reinforced HSC.…”
Section: Introductionmentioning
confidence: 99%
“…Concrete is weak in transferring the tensile stresses and eventually developing cracks under tension 1–3 . The primary purpose of adding fibers in concrete is to improve the tensile strength and reduce brittle behavior 4,5 .…”
Section: Introductionmentioning
confidence: 99%